The potential of polyhalite as a multi-nutrient fertilizer for sugarcane - Bejarano Herrera, Wilfrand Ferney (2019)
Sugarcane is one of the crops with the highest extraction of macronutrients from the soil, both in cane-plant and ratoon crops, being critical its reposition by means of fertilizers. In the Brazilian sugarcane agrosystem, the supply of elements, such as, potassium (K), calcium (Ca), magnesium (Mg) and sulfur (S) is commonly performed by fertilizers, like potassium chloride, and soil amendments, such as, lime and phosphogypsum, producing high costs by sole application. In this context, the study aimed to determine the potential of polyhalite as a multi-nutrient source of K, Ca, Mg and S and its effects on yield and quality of sugarcane. In order to reach this objective, the study was divided into three stages: i) field evaluation in low K soil comparing doses of POLY with the combined application of KCl and GYP to evaluate yield, quality, soil chemical parameters, straw and stalk macronutrient content in two sugarcane varieties. ii) elemental, mineralogical and release characterization of the polyhalite (POLY) and potassium chloride (KCl) by the use of micro X-ray fluorescence spectrometry (µXRF) and X-ray diffraction spectrometry; and (iii) evaluation under glasshouse conditions to evaluate the residual effect of the application of POLY dosages contrasted to the application of KCl, GYP and kieserite (KIE) in the leaf macronutrients content, and biomass production in an Oxisol with a low level of K. Based on the field experiment, the application of calcium (Ca), magnesium (Mg), sulfur (S) and mainly potassium (K), irrespective the source applied, affected positively the yield in sugarcane. Related to the dosage, application of 105 kg K2O ha-1, which corresponds to farmer\'s recommended dosage, promoted the highest stalk yields for both varieties, CV7870 and RB867515. This dosage keeps the adequate nutritional status of sugarcane ratoon and enhance the K content in stalk, promoting the accumulation of sucrose in this plant organ. In relation to the soil parameters, for the variety RB867515, after cultivation, most of the nutrient concentration remained in soil were not significant compared to control, suggesting that as much fertilizer is applied this variety will uptake and export. In contrast, the variety CV7870 showed higher remained values for soil Ca, Mg and S in the treatments compared to the control after cultivation, indicating a residual effect, irrespective the treatment. Based on the laboratory results, KCl granule in the moisture low-K sandy Oxisol has rapidly promoted dissolution of nutrients and then released Cl- and K+, being susceptible for leaching, whereas POLY granule performed as a slow-release fertilizer due to its low solubility compared to KCl, enhancing residual effect over time. The results of the glasshouse showed that DM yield and nutrient uptake were more correlated to high K dosages applied (42 and 63 mg kg-1) and K sources containing Ca and S in the formulation (POLY, KCl+GYP+KIE and ½KCl ½POLY), for both cane-plant and ratoon. However, when these sources were provided at the lowest dosage (21 mg kg-1) it was observed superior agronomic efficiency for all added nutrients, indicating that a combination of KCl and POLY can be used more efficiently as K source for sugarcane. Taking together, both experiments, in the field and in the greenhouse, showed that polyhalite is suitable to supply K, Ca, Mg and S at the farmer\'s dosage recommendation. Furthermore, the blend of 50% polyhalite and 50% KCl could be adopted for farmers minimizing plant nutrient losses with a more balanced nutrition.